Route Choice in Subway Station during Morning Peak Hours: A Case of Guangzhou Subway - Jie Xu; Yao Ning; Heng Wei; Wei Xie; Jianyuan Guo; Limin Jia; Yong Qin (Discrete Dynamics in Nature and Society)
This paper is aimed at crowding phenomenon in the subway. As passengers are inclined to choose the route with minimum disutility, we put forward a route choice model which is constructed to achieve minimum objective function of feasibility for the optimal solution. Meanwhile we set passenger volume threshold values according to capacity of facilities. In the case of actual capacity exceeding the threshold, the decision node of constrained route will be selected; computing procedure about searching decision points will be presented. Then we should set rational restrictions at the decision node of the minimum utility function route to prevent too many passengers’ access to platform. Through certification, this series of methods can effectively ensure the safety of the station efficient operation.